Circuit mathematical models of electric devices - Tchaban, Vasyl (Publishing House of Lviv Polytechnic National University, 2014)
On the basis of the main laws of electromagnetic circuit theory we propose general approach to creating four concepts of circuit mathematical models of electrical devices. It is shown that by the same assumptions their discrete analogues are different. Owing to this idea, the real possibility to present differential equatons of industrial electrical devices (static and electromechanic ones) and the systems formed by them in the normalized Cauchy form is shown, which is very important for the analysis of the long-term processes. На підставі основних положень теорії електро-магнетних кіл, пропоновано загальний підхід до побудови чотирьох видів колових математичних моделей електротехнічних пристроїв, кожна з яких має своє призначення. Показано, що при однакових допущеннях їхні дискретні аналоги суттєво відрізняються. На цій підставі вперше отримано реальну можливість представити диференціальні рівняння промислових електротехнічних пристроїв (статичних і електромеханічних) та систем, що вони утворюють, у нормальній формі Коші, що дуже важливо для аналізу тривалих перехідних процесів.
Колові математичні моделі електротехнічних пристроїв
Keywords: electromagnetic circuit theory; four mathematical models of electrical devices